A CORRELATIONAL STUDY BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION AT ECONOMIC FACULTY OF ALKHAIRAAT UNIVERSITY - Afifah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This research is a correlational study with two variables – variable X standing for vocabulary mastery and variable Y standing for reading comprehension. There were three research questions: (1) What is the level of correlation between variable X and variable Y?; (2) How significant is the contribution that can be given by variable X toward variable Y?; and (3) Is there positive correlation between variable X and variable Y? The sample of this research was fifty students of the first semester at Economic Faculty of Alkhairaat University. The instruments were tests and questionnaire. Through tests, it was found that: (1) The level of correlation between variable X and variable Y was strong; (2) The significant contribution given by variable X toward variable Y was 52.8%, meaning variable X gave much contribution to variable Y; and (3) There was positive correlation between variable X and variable Y since the value of r-counted (0.727) was higher than the value of r-table (0.279). Through questionnaire, 46% respondents agreed that vocabulary took a role in helping them to comprehend English texts, meaning the more vocabulary they have, the better they are in comprehending English texts.